Oxide optical glass and preparation method thereof
By combining B3+, Si4+, La3+, Y3+, Nb5+, Zn2+ and Sn4+ components in specific proportions, low-cost, high-performance oxide optical glass is prepared, which solves the problems of high raw material cost, high melting temperature and low transmittance in the ultraviolet light band, and improves the stability and formability of the glass.
Patent Information
- Application Number
- CN202510898295.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-30
- Publication Date
- 2025-09-23
Smart Images

Figure BDA0005478171070000121 
Figure BDA0005478171070000122 
Figure BDA0005478171070000131
Abstract
Description
Technical Field
[0001] The invention relates to oxide optical glass and a preparation method thereof, belonging to the field of oxide optical glass. Background Art
[0002] High refractive index and low dispersion oxide optical glass can simplify the optical system, eliminate spherical aberration, chromatic aberration and image distortion, expand the field of view of the lens, and play an important role in improving the imaging quality of optical instruments. It can also promote the development of miniaturization and lightweight of lenses. d ) between 1.86 and 1.92 and Abbe number (υd) between 36 and 42 plays an extremely important role in improving the imaging quality of optical systems.
[0003] To meet the functional requirements of high-refractive-low-dispersion oxide optical glass, the glass network-forming agents SiO2 and B2O3 are low in content, and contain large amounts of macromolecular oxides such as La2O3, Y2O3, Gd2O3, and Nb2O5 that contribute to the glass network aggregation. This results in a narrow glass-forming range, high crystallization temperature, strong crystallization tendency, and low viscosity, leading to defects such as streaks and bubbles in the product that are difficult to eliminate. Therefore, the existing oxide optical glass composition needs further exploration to find an oxide optical glass composition with stable performance, low cost, and ease of production.
[0004] Chinese patent application CN111018343A discloses a refractive index n d is above 1.86, Abbe number υ d The oxide optical glass has a content of 39 to 42, and its composition contains 0.01% to 10.0% Gd2O3 and 3% to 13% ZrO2 in mole percentage.
[0005] Chinese patent application CN118515427A discloses a refractive index n d The Abbe number is 1.86~1.91, d The oxide optical glass has an O content of 37 to 41, and its composition, expressed in weight percentage, contains 2 to 9.5% Gd2O3, 3 to 10% ZrO2 and 0.1 to 5% TiO2.
[0006] Chinese patent application CN110835229A discloses a refractive index n d Greater than 1.86, Abbe number υ d Greater than 38.8 oxide optical glass, its composition contains 1 to 15 weight percent of ZrO2 and 10 to 35 weight percent of Gd2O3.
[0007] Chinese patent application CN119241062A discloses a refractive index n d The Abbe number is 1.87 to 1.94. dThe invention relates to a 33-41 oxide optical glass, wherein the composition thereof contains 2-15% ZrO2 by weight.
[0008] Chinese patent application CN115385569A discloses a refractive index n d The Abbe number is 1.87 to 1.94. d The oxide optical glass has an Oxide content of 33 to 41 and contains 2 to 15% ZrO2 in weight percentage.
[0009] Chinese patent application CN115321812A discloses an oxide optical glass with an Abbe number υd of 35 to 39, wherein the glass composition contains 5.75% to 12% by mass of TiO2 and more than 0% to 4.85% by mass of ZrO2.
[0010] Chinese patent application CN116891339 A discloses a crystalline silicon nanostructured carbon ... d The oxide optical glass has a mass ratio of Gd2O3 to the total content of La2O3, Gd2O3, Y2O3 and Yb2O3 (Gd2O3 / (La2O3+Gd2O3+Y2O3+Yb2O3)) of 40.0 or more and 44.0 or less, and the mass ratio of Gd2O3 to the total content of La2O3, Gd2O3, Y2O3 and Yb2O3 (Gd2O3 / (La2O3+Gd2O3+Y2O3+Yb2O3)) is 0.10 or more and 0.45 or less, that is, the glass composition contains the expensive raw material Gd2O3.
[0011] Among these disclosed oxide optical glasses, some contain the expensive raw material Gd2O3, resulting in high raw material costs for the oxide optical glass; some contain ZrO2 with a melting point as high as 2700°C. ZrO2 is one of the materials with the highest melting points among oxides, resulting in a high melting temperature for the glass raw materials and strong corrosiveness to the melting equipment. The oxidation, volatilization, corrosion and aging of Pt at high temperatures are aggravated, which is not conducive to reducing the production cost of the glass. In addition, the scattering of Pt particles will absorb light in the wavelength range of 380 to 400 nm, reducing the transmittance of the glass and worsening the coloration of the glass; some contain TiO2. The Ti element absorbs ultraviolet light, which is not conducive to the transmission of the ultraviolet light band of the optical system. Summary of the Invention
[0012] Problems to be solved by the invention
[0013] In view of the technical problems existing in the prior art, the present invention provides a refractive index (n d ) is 1.86~1.92, Abbe number (υ d ) is 36 to 42. The oxide optical glass of the present invention is low-cost, further helping to reduce the cost of optical systems. The oxide optical glass of the present invention has excellent performance and is helpful in improving the transmittance of optical systems in the ultraviolet band.
[0014] Furthermore, the present invention also provides a method for preparing oxide optical glass, which is simple and easy to prepare, and the raw materials are easy to obtain, and is suitable for mass production.
[0015] Solutions for solving problems
[0016] The present invention provides an oxide optical glass, wherein the oxide optical glass comprises the following components in terms of cation molar percentage:
[0017] B 3+ : 15% to 40%, preferably 18% to 38%;
[0018] Si 4+ : 2% to 25%, preferably 4% to 22%;
[0019] La 3+ : 17% to 42%, preferably 20% to 40%;
[0020] Y 3+ : 0% to 15%, preferably 0% to 12%;
[0021] Nb 5+ : 2% to 15%, preferably 6% to 14%;
[0022] Zn 2+ : 6% to 25%, preferably 10% to 19%;
[0023] Sn 4+ : 0% to 2.0%, preferably 0.5% to 1.6%;
[0024] The refractive index of the oxide optical glass is 1.86-1.92, and the Abbe number is 36-42.
[0025] According to the oxide optical glass of the present invention, B 3+ The molar percentage of Si 4+ The sum of the molar percentages ∑(B 3+ +Si 4+ ) is 30% to 55%; preferably 32% to 52%.
[0026] According to the oxide optical glass of the present invention, B 3+ The molar percentage of Si 4+ The molar percentage ratio B 3+ / Si 4+ It is 0.5 to 5.5, preferably 1.1 to 4.9.
[0027] According to the oxide optical glass of the present invention, La 3+ The molar percentage of Y 3+The sum of the molar percentages ∑(La 3+ +Y 3+ ) is 20% to 46%, preferably 22% to 45%.
[0028] According to the oxide optical glass of the present invention, wherein Y 3+ The molar percentage of La 3+ The molar percentage ratio Y 3+ / La 3+ It is 0 to 0.8, preferably 0 to 0.5.
[0029] According to the oxide optical glass of the present invention, Zn 2+ The molar percentage of B 3+ The molar percentage of Si 4+ The ratio of the sum of the molar percentages of Zn 2+ / ∑(B 3+ +Si 4+ ) is 0.1 to 0.8, preferably 0.1 to 0.6.
[0030] According to the oxide optical glass of the present invention, the oxide optical glass does not contain Zr 4+ 、Ti 4+ 、W 6+ 、Gd 3+ 、Ba 2+ 、Bi 3+ 、Ge 4+ 、Ta 5+ 、Yb 3+ 、Li + and Te 4+ One or a combination of two or more.
[0031] According to the oxide optical glass of the present invention, the density of the oxide optical glass is 4.90 g / cm 3 the following;
[0032] The wavelength λ when the external transmittance of the oxide optical glass is 70% 70 Below 380nm, the wavelength at which the external transmittance is 5% is below 330nm;
[0033] The thermal expansion coefficient of the oxide optical glass is α -50 / 80℃ 70×10 -7 / K or less.
[0034] According to the oxide optical glass of the present invention, the Knoop hardness HK of the oxide optical glass is 650×10 7 Pa or above;
[0035] The elastic modulus E of the oxide optical glass is greater than 115 GPa.
[0036] The present invention also provides a method for preparing the oxide optical glass according to the present invention, which comprises: weighing the raw materials of each component according to a proportion, mixing them uniformly, melting them, and then pouring or leaking them into a forming mold, or directly pressing them into shape.
[0037] Effects of the Invention
[0038] The oxide optical glass of the present invention has low cost, which is further beneficial to reducing the cost of the optical system. The oxide optical glass of the present invention has excellent performance, which is beneficial to improving the transmittance of the optical system in the ultraviolet band.
[0039] The present invention also provides a method for preparing oxide optical glass, which is simple and easy to implement, and the raw materials are easy to obtain, and is suitable for mass production. DETAILED DESCRIPTION
[0040] Various exemplary embodiments, features, and aspects of the present invention will be described in detail below. The word "exemplary" is used herein to mean "serving as an example, embodiment, or illustration." Any embodiment described herein as "exemplary" is not necessarily to be construed as superior or preferred over other embodiments.
[0041] In addition, numerous specific details are provided in the following detailed description to better illustrate the present invention. Those skilled in the art will appreciate that the present invention can be practiced without certain specific details. In other instances, methods, means, equipment, and steps well known to those skilled in the art are not described in detail in order to highlight the main points of the present invention.
[0042] Unless otherwise stated, the units used in this specification are international standard units, and the numerical values and numerical ranges appearing in the present invention should be understood to include the inevitable systematic errors in industrial production.
[0043] In this specification, the use of "may" includes both the meaning of performing a certain process and the meaning of not performing a certain process.
[0044] In this specification, references to "some specific / preferred embodiments," "other specific / preferred embodiments," "embodiments," etc., mean that the specific elements (e.g., features, structures, properties, and / or characteristics) described in connection with the embodiments are included in at least one embodiment described herein, and may or may not be present in other embodiments. In addition, it should be understood that the elements may be combined in various embodiments in any suitable manner.
[0045] In this specification, the numerical range expressed using "a numerical value A to a numerical value B" means a range including the endpoints A and B.
[0046] The present invention first provides an oxide optical glass comprising the following components in terms of cation mole percentage:
[0047] B 3+ : 15% to 40%, preferably 18% to 38%;
[0048] Si 4+ : 2% to 25%, preferably 4% to 22%;
[0049] La 3+ : 17% to 42%, preferably 20% to 40%;
[0050] Y 3+ : 0% to 15%, preferably 0% to 12%;
[0051] Nb 5+ : 2% to 15%, preferably 6% to 14%;
[0052] Zn 2+ : 6% to 25%, preferably 10% to 19%;
[0053] Sn 4+ : 0% to 2.0%, preferably 0.5% to 1.6%;
[0054] The refractive index of the oxide optical glass (n d ) is 1.86~1.92, and the Abbe number (υ d ) is 36 to 42.
[0055] The oxide optical glass of the present invention has low cost, which is further beneficial to reducing the cost of the optical system. The oxide optical glass of the present invention has excellent performance, which is beneficial to improving the transmittance of the optical system in the ultraviolet band.
[0056] The raw material introduction method adopts various forms of compounds that can introduce their corresponding contents. In the following description, each cation is expressed in molar percentage.
[0057] B 3+ It is a glass former that can improve the glass's solubility and resistance to devitrification. 3+ The molar percentage of La is less than 15%, which will reduce the 3+ 、Nb 5+ The amount of plasma dissolved in the glass composition cannot promote the melting of the components of the oxide optical glass at a temperature of 1350°C or below; if B 3+If the molar percentage of B is greater than 40%, the refractive index of the obtained glass cannot meet the requirements of the present invention, and the volatilization during the melting process increases and causes fluctuations in the glass constant and stripes, increasing the difficulty of mass production. Therefore, in the present invention, B 3+ The molar percentage is 15% to 40%, preferably 18% to 38%, for example, 20% to 35%.
[0058] Si 4+ It is also a glass former that can increase the viscosity of molten glass, reduce the erosion of molten glass on melting equipment, and reduce the coloring of glass. 4+ Forming a three-dimensional network of silicon-oxygen tetrahedrons, dense and strong, 3+ The loose chain layered network formed is different. 4+ The introduction of La can strengthen the loose boron oxide triangle [BO3] network and make it dense, thereby increasing the high temperature viscosity of the glass and maintaining a viscosity suitable for molten glass molding; at the same time, with the addition of the three-dimensional network of silicon oxide tetrahedron, the glass network isolates La 3+ 、Nb 5+ The enhanced plasma capacity increases the crystallization threshold and improves the anti-crystallization performance of the glass. 4+ When the molar content of Si is less than 2%, the anti-crystallization performance of the glass deteriorates, and the effect of improving the viscosity of the molten glass molding is not significant, which is not conducive to molding control. 4+ When the molar content of Si is higher than 25%, the viscosity of the glass liquid at high temperature is too high, which is not conducive to the removal of bubbles. 4+ The molar percentage is 2% to 25%, preferably 4% to 22%, for example, 6% to 20%.
[0059] The inventors found through a large number of experiments that: 3+ The molar percentage of Si 4+ The sum of the molar percentages ∑(B 3 + +Si 4+ ) has a decisive influence on the formation characteristics of glass. If ∑(B 3+ +Si 4+ ) is too low, stable glass cannot be formed; if ∑(B 3+ +Si 4+ ) is too high, the refractive index and Abbe number of the obtained glass are difficult to reach the specific range of the present invention. Therefore, in the present invention, B 3+ The molar percentage of Si 4+ The sum of the molar percentages ∑(B 3+ +Si 4+ ) is 30% to 55%; preferably 32% to 52%, more preferably 33% to 48%, for example: 35% to 45%, etc.
[0060] At the same time, B 3+ The molar percentage of Si 4+ The molar percentage ratio B 3+ / Si 4+ It has a significant impact on the crystallization performance of glass. 3+ / Si 4+ When the value is between 0.5 and 5.5, the formed glass is more stable and has a lower tendency to crystallize. 3+ / Si 4+ When it is less than 0.5, crystallization particles are likely to appear inside the glass liquid, and the crystallization temperature of the glass is greater than 1350℃; when B 3+ / Si 4+ When B is greater than 5.5, the surface of the glass is prone to wrinkle crystallization, or even glass cannot be formed. 3+ The molar percentage of Si 4+ The molar percentage ratio B 3+ / Si 4+ It is 0.5 to 5.5, preferably 1.1 to 4.9, for example 1.2 to 4.0.
[0061] La 3+ It is an effective component for increasing the refractive index of glass and reducing dispersion, and is the main component of oxide optical glass. 3 + When the molar percentage of La is less than 17%, the refractive index and Abbe number of the glass will be difficult to reach the above-mentioned specific range; 3+ When the molar percentage of La is greater than 42%, the devitrification tendency of the glass increases and the liquidus temperature rises. 3+ The molar percentage of is 17% to 42%, preferably 20% to 40%, such as 24% to 34%.
[0062] In the present invention, Y 3+ with La 3+ The performance is basically the same, which can make the oxide optical glass have a higher refractive index and lower dispersion. Proper addition in the glass composition can improve the crystallization performance of the glass. However, when Y 3+ When the molar percentage of Y is higher than 15%, the devitrification resistance deteriorates. 3+ The molar percentage is 0% to 15%, preferably 0% to 12%, for example 0% to 10%.
[0063] The inventors found through a large number of experiments that: La 3+ The molar percentage of Y 3+ The sum of the molar percentages ∑(La 3+ +Y 3+) has a certain influence on the performance of oxide optical glass. If ∑(La 3+ +Y 3+ ) is too high, the performance of the oxide optical glass will deteriorate. 3+ +Y 3+ ) is too low, the optical constants of the glass will be difficult to reach the range of the present invention. Therefore, in the present invention, La 3+ The molar percentage of Y 3+ The sum of the molar percentages ∑(La 3+ +Y 3+ ) is 20% to 46%, preferably 22% to 45%, for example: 24% to 42%.
[0064] Y 3+ The molar percentage of La 3+ The molar percentage ratio Y 3+ / La 3+ It has a great influence on the crystallization performance of the glass. 3+ / La 3+ When Y is too high, the glass crystallization performance deteriorates. 3+ The molar percentage of La 3+ The molar percentage ratio Y 3+ / La 3+ It is 0 to 0.8, preferably 0 to 0.5, for example, 0 to 0.4.
[0065] Nb 5+ It has the effect of increasing the refractive index of oxide optical glass, improving chemical stability and crystallization performance. 5+ When the molar percentage of Nb is less than 2%, this effect is not obvious; 5+ When the molar percentage of Nb is higher than 15%, the crystallization performance of the glass will gradually deteriorate, and it is difficult to achieve the expected optical properties of the present invention. 5+ The molar percentage is 2% to 15%, preferably 6% to 14%, for example 7% to 13%.
[0066] Zn 2+ It can adjust the refractive index and dispersion of glass, improve the anti-crystallization performance of glass, reduce the transition temperature of glass, and enhance the stability of glass. 2+ It can also reduce the high temperature viscosity of the glass, so that the glass can be melted at a lower temperature, thereby improving the transmittance of the glass. 2+ When the molar percentage of Zn is lower than 6%, the anti-crystallization performance of the glass deteriorates; when the molar percentage of Zn is lower than 6%, the anti-crystallization performance of the glass deteriorates. 2+When the molar percentage of Zn is higher than 25%, the refractive index of the glass decreases, failing to meet the requirements of the present invention, and increasing the corrosion of the melting device during the melting process, making it difficult to melt glass with good intrinsic quality. 2+ The molar percentage is 6% to 25%, preferably 10% to 19%, for example 10.5% to 17.5%.
[0067] The inventors have found through a large number of experiments that Zn 2+ The molar percentage of B 3+ The molar percentage of Si 4+ The ratio of the sum of the molar percentages of Zn 2+ / ∑(B 3+ +Si 4+ ) has a great influence on the glass forming properties. When Zn 2+ / ∑(B 3+ +Si 4+ ) is too low, the molten glass is prone to internal crystallization, resulting in a high crystallization temperature of the glass; when Zn 2+ / ∑(B 3+ +Si 4+ ) is too high, the molten glass is prone to surface crystallization, resulting in a high glass crystallization temperature. 2+ The molar percentage of B 3+ The molar percentage of Si 4+ The ratio of the sum of the molar percentages of Zn 2+ / ∑(B 3+ +Si 4+ ) is 0.1 to 0.8, preferably 0.1 to 0.6, for example 0.1 to 0.5.
[0068] Sn 4+ Ions have the function of improving optical constants, increasing resistance to devitrification and chemical stability. Sn atoms have empty d orbitals and can form chemical bonds with oxygen atoms in the glass network. In the oxide optical glass of the present invention, Sn 4+ It can connect with boron-oxygen tetrahedron and silicon-oxygen tetrahedron through Sn-O bond, incorporate itself into the glass network structure, and affect the polymerization degree of silicon-oxygen tetrahedron or other structural units in the glass. 4+ ions, the network is reconnected through coordination, which plays a role in adjusting the density of the glass structure and enhancing the network connectivity, thereby improving the chemical stability and mechanical strength of the glass and improving the crystallization performance of the glass. 4+ SnO2 has a high specific gravity. If Sn 4+ If the molar percentage of Sn is higher than 2%, it will sink to the bottom during the melting process, increasing the melting difficulty and being unfavorable for the melting of glass. 4+The molar percentage is 0% to 2.0%, preferably 0.5% to 1.6%, for example 0.8% to 1.4%.
[0069] Furthermore, the anion in the oxide optical glass of the present invention is O 2- .
[0070] Furthermore, the oxide optical glass of the present invention does not contain Zr 4+ 、Ti 4+ 、W 6+ 、Gd 3+ 、Ba 2+ 、Bi 3+ 、Ge 4+ 、Ta 5+ 、Yb 3+ 、Li + and Te 4+ One or a combination of two or more.
[0071] Specifically, the oxide optical glass of the present invention may not contain W which reduces the ultraviolet light transmittance of the glass. 6+ and Ti 4+ ; It may not contain Zr with high melting point 4+ , thereby reducing the melting temperature of the glass, reducing the corrosion of the melting device during the glass production process, reducing the production cost of the glass and improving the short-wave transmittance of the glass; it can be free of Te which is easy to cause volatile streaks 4+ , avoid the generation of volatile streaks; Ba can be omitted 2+ , reducing the corrosion of the melting device during the glass production process and reducing the production cost of the glass; it also does not require the introduction of expensive Ge 4+ 、Ta 5+ 、Yb 3+ And other ingredients.
[0072] In addition, in order to better achieve the purpose of the present invention, the oxide optical glass of the present invention may not contain Li which may corrode the melting device and destroy the glass network structure and deteriorate the crystallization performance of the glass. + and Yb, which has an absorption peak in the ultraviolet band 3+ . Due to Bi 3+ The reaction with Pt at 1200-1250°C increases the difficulty of melting the glass, which is not conducive to melting glass with good intrinsic quality. Therefore, the oxide optical glass of the present invention preferably does not contain Bi. 3+ .
[0073] Furthermore, to ensure the spectral transmittance of the oxide optical glass described herein, the oxide optical glass provided herein does not artificially introduce any coloring elements other than the aforementioned components: V, Mo, Cr, Mn, Fe, Co, Ni, Cu, and Ag. Furthermore, compounds containing the following harmful elements: Th, Cd, Tl, Os, Be, Se, Pb, As, Hg, and fluorides are also not artificially introduced.
[0074] Furthermore, the oxide optical glass of the present invention has one of the following characteristics:
[0075] The density of the oxide optical glass is 4.90 g / cm 3 the following;
[0076] The wavelength λ when the external transmittance of the oxide optical glass is 70% 70 Below 380nm, the wavelength at which the external transmittance is 5% is below 330nm;
[0077] The thermal expansion coefficient of the oxide optical glass is α -50 / 80℃ 70×10 -7 / K or less.
[0078] The Knoop hardness HK of the oxide optical glass is 650×10 7 Pa or above;
[0079] The elastic modulus E of the oxide optical glass is greater than 115 GPa.
[0080] In addition, in the present invention, the powder method water resistance D of the oxide optical glass is W Or / and surface moisture resistance stability R C or / and surface acid resistance R A or / and washing resistance RP(S) or / and alkali resistance R OH (S) can be level 1; the powder method acid resistance of the oxide optical glass D A Can be level 1 or level 2.
[0081] In addition, the bubble degree of the oxide optical glass is above grade A, preferably above grade A0, more preferably grade A00; the anti-crystallization performance of the oxide optical glass is above grade C, preferably above grade B, more preferably grade A.
[0082] The present invention also provides a method for preparing the oxide optical glass according to the present invention, comprising: weighing the raw materials of each component according to a proportion, mixing them uniformly, melting them, and then pouring or leaking them into a forming mold, or directly pressing them into shape.
[0083] Specifically, raw materials used in oxide optical glass with a purity greater than 99% are weighed in the specified proportions, mixed thoroughly, and then stirred and melted in a crucible made of a precious metal such as platinum at 1350-1400°C for 2-4 hours. After melting and stirring, the mixture is poured into a mold and slowly cooled to produce the glass sample, which is then processed into oxide optical glass samples.
[0084] The present invention also provides an optical element comprising the oxide optical glass according to the present invention.
[0085] Example
[0086] The embodiments of the present invention will be described in detail below with reference to the examples, but it will be understood by those skilled in the art that the following examples are merely illustrative of the present invention and should not be construed as limiting the scope of the invention. Where specific conditions are not specified in the examples, the methods were performed according to conventional conditions or the conditions recommended by the manufacturer. Where the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be obtained commercially.
[0087] Examples 1-30
[0088] Introducing B 3+ 、Si 2+ 、La 3+ 、Y 3+ 、Nb 5+ 、Zn 2+ and Sn 4+ The raw materials are all selected from boric acid, quartz sand, lanthanum trioxide, yttrium trioxide, niobium pentoxide, zinc oxide and tin dioxide, etc., which are used in oxide optical glass with a purity greater than 99%. They are weighed and proportioned according to the molar percentage of ions shown in Tables 1 to 5, and then mixed evenly. The mixture is added to a platinum crucible and melted at a temperature of 1350°C for about 3 hours. After stirring evenly, the mixture is poured into a mold and slowly cooled to obtain these glass samples, which are then processed into oxide optical glass samples for performance testing.
[0089] Performance Testing
[0090] The refractive index (n) of the oxide optical glasses prepared in Examples 1-30 and Comparative Examples 1-5 was tested using the following test method. d ), Abbe number (υ d ), when the external transmittance reaches 70%, the corresponding wavelength is λ 70 , when the external transmittance reaches 5%, the corresponding wavelength is λ5, and the expansion coefficient is α -50 / 80℃ , density (ρ), Knoop hardness HK, elastic modulus E, powder method water resistance D W , Powder method acid resistance D A , surface moisture resistance stability R C, surface acid resistance R A , washing resistance RP (S), alkali resistance R OH (S), and liquidus temperature (L T )The test results are shown in the table.
[0091] 1. Refractive index n d , Abbe number υ d :
[0092] The test was carried out according to the test method of GB / T7962.1-2010.
[0093] 2. Density (ρ)
[0094] The measurement shall be carried out in accordance with the method specified in GB / T7962.20-2010.
[0095] 3. Lambda 70 and λ5
[0096] A glass sample with a thickness of 10 ± 0.1 mm and parallel optically polished planes was prepared, and a beam of light with an intensity of I was incident on the glass sample from a direction perpendicular to the planes. in The intensity of the transmitted light is measured I out , the intensity ratio I out / I in It is called the external transmittance of glass.
[0097] In the wavelength range of 200 to 700 nm, the wavelength corresponding to the external transmittance reaching 70% is recorded as λ 70 The wavelength corresponding to when the external transmittance reaches 5% is recorded as λ5.
[0098] 4. Thermal expansion coefficient α -50 / 80℃
[0099] Test the thermal expansion coefficient α at -50~80℃ according to the test method specified in GB / T7962.18-2010 -50 / 80 ℃.
[0100] 5. Knoop hardness HK
[0101] The test is carried out according to the test method specified in GB / T7962.18-2010.
[0102] The hardness was measured using a microhardness tester. A square pyramid diamond indenter with symmetrical angles of 172°30′ and 130° was used to apply a load of 0.98N to the sample surface. The load was maintained for 15 seconds until a mark appeared. The load was removed and the length of the diagonal line of the indentation on the sample was observed and measured using a microscope. The formula HK = 1.451×F÷(d 2) to calculate Knoop hardness. Where: HK represents Knoop hardness, ×10 7 Pa; F represents the pressurized load, N; d represents the length of the diagonal line of the indentation, mm.
[0103] 6. Elastic modulus E
[0104] The test is carried out according to the test method specified in GB / T7962.6-2010.
[0105] 7. Water resistance by powder method D W , Powder method acid resistance D A
[0106] According to the test method of JB / T10576-2006, the water resistance of the obtained oxide optical glass is tested for chemical stability. W , acid resistance D A Conduct a test.
[0107] 8. Surface moisture resistance stability R C , surface acid resistance R A
[0108] Under the conditions of temperature 50°C and relative humidity 85%, the stability of oxide optical glass against humid atmosphere is divided into three levels according to the time required for hydrolysis spots to form on the polished glass surface, as shown in Table A below.
[0109] Table A
[0110] level 1 2 3 Time (h) >20 5~20 <5
[0111] In the presence of 0.1N (pH=2.9) acetic acid solution at 50°C, the acid resistance of oxide optical glass is divided into three levels according to the time required for interference color to appear on the polished surface of the glass, or for the surface to become mottled or fall off, as shown in Table B below.
[0112] Table B
[0113] level 1 2 3 Time (h) >5 1~5 <1
[0114] 9. Washing resistance RP(S), alkali resistance R OH (S)
[0115] A sample with six polished sides and a size of 40 mm × 40 mm × 5 mm was immersed in a well-stirred sodium hydroxide aqueous solution at a constant temperature of 50°C ± 3°C and a concentration of 0.01 mol / l for 15 hours. The average leaching mass per unit area was expressed in mg / (cm 2 15h), the alkali resistance stability of oxide optical glass R OH (S) is divided into five levels, as shown in Table C below.
[0116] Table C
[0117]
[0118] A 35mm×35mm×8mm sample with six polished sides was immersed in a well-stirred Na5P3O solution with a constant temperature of 50℃±3℃ and a concentration of 0.01mol / L. 10 1 hour in aqueous solution. According to the average value of leaching mass per unit area, the unit is mg / (cm 2 h), the washing resistance stability RP(S) of oxide optical glass is divided into five levels, as shown in Table D below.
[0119] Table D
[0120]
[0121] 10. Bubble degree
[0122] The bubble degree of oxide optical glass is tested according to the method specified in GB / T7962.8-2010.
[0123] 11. Anti-crystallization performance
[0124] The test method for the anti-crystallization performance of the oxide optical glass of the present invention is as follows: a glass sample of 11mm×23mm×24mm in size is placed in a semicircular porcelain box with a radius of 15mm and a depth of 15mm. The porcelain box containing the sample is subjected to a heating and cooling cycle. The heating and cooling process is: heating to (Tg+230)℃ in a test furnace for 15 minutes, taking out and cooling to 200℃ in a mesh belt annealing furnace. After three heating and cooling cycles, take out the glass sample and naturally cool it to room temperature in an atmospheric environment. After observing the overall softening degree and devitrification of the glass with the naked eye, and then grinding and polishing the glass sample, observe the inside of the glass through a microscope to confirm the presence of crystallization particles. The anti-crystallization performance of the glass is judged according to Table E below, with grade A being the best and grade E being the worst.
[0125] Table E: Classification and judgment criteria of anti-crystallization performance
[0126]
[0127] Table 1 Examples 1 to 6
[0128]
[0129] Table 2 Examples 7 to 12
[0130]
[0131] Table 3 Examples 13 to 18
[0132]
[0133] Table 4 Examples 19 to 24
[0134]
[0135] Table 5 Examples 25-30
[0136]
[0137] It can be seen from Tables 1-5 that the oxide optical glasses of Examples 1 to 30 of the present invention not only have a refractive index (n d ) and Abbe number (υ d ), density is 4.90g / cm 3 Below, the wavelength λ when the external transmittance is 70% 70 Below 380nm, the wavelength when the external transmittance is 5% is below 330nm; the thermal expansion coefficient α -50 / 80℃ 70×10 -7 / K or less, powder method water resistance D W , surface moisture resistance stability R C , surface acid resistance R A , washing resistance RP (S), alkali resistance R OH (S) is level 1, powder method acid resistance D A It is grade 2, and its hardness HK is 650×10 7 Pa or above, the elastic modulus E of the optical glass is above 115 GPa, the bubble degree is above grade A, and the anti-crystallization performance is above grade C.
[0138] It should be noted that, although the technical solutions of the present invention are described with specific examples, those skilled in the art will appreciate that the present invention should not be limited thereto.
[0139] While various embodiments of the present invention have been described above, the above descriptions are intended to be illustrative, non-exhaustive, and not limited to the disclosed embodiments. Many modifications and variations will be apparent to those skilled in the art without departing from the scope and spirit of the described embodiments. The terminology used herein is selected to best explain the principles of the embodiments, their practical applications, or technological improvements in the marketplace, or to enable others skilled in the art to understand the embodiments disclosed herein.
Claims
1. An oxide optical glass, characterized in that: Contains the following components in terms of cation molar percentage: B 3+ : 15% to 40%, preferably 18% to 38%; Si 4+ : 2% to 25%, preferably 4% to 22%; La 3+ : 17% to 42%, preferably 20% to 40%; Y 3+ : 0% to 15%, preferably 0% to 12%; Nb 5+ : 2% to 15%, preferably 6% to 14%; Zn 2+ : 6% to 25%, preferably 10% to 19%; Sn 4+ : 0% to 2.0%, preferably 0.5% to 1.6%; The refractive index of the oxide optical glass is 1.86-1.92, and the Abbe number is 36-42.
2. The oxide optical glass according to claim 1, characterized in that B 3+ The molar percentage of Si 4+ The sum of the molar percentages ∑(B 3+ +Si 4+ ) is 30% to 55%; preferably 32% to 52%.
3. The oxide optical glass according to claim 1 or 2, characterized in that: B 3+ The molar percentage of Si 4+ The molar percentage ratio B 3+ / Si 4+ It is 0.5 to 5.5, preferably 1.1 to 4.
9.
4. The oxide optical glass according to any one of claims 1 to 3, characterized in that: La 3+ The molar percentage of Y 3+ The sum of the molar percentages ∑(La 3+ +Y 3+ ) is 20% to 46%, preferably 22% to 45%.
5. The oxide optical glass according to any one of claims 1 to 4, characterized in that: Y 3+ The molar percentage of La 3+ The molar percentage ratio Y 3+ / La 3+ It is 0 to 0.8, preferably 0 to 0.
5.
6. The oxide optical glass according to any one of claims 1 to 5, characterized in that: Zn 2+ The molar percentage of B 3+ The molar percentage of Si 4+ The ratio of the sum of the molar percentages of Zn 2+ / ∑(B 3+ +Si 4+ ) is 0.1 to 0.8, preferably 0.1 to 0.
6.
7. The oxide optical glass according to any one of claims 1 to 6, characterized in that: The oxide optical glass does not contain Zr 4+ 、Ti 4+ 、W 6+ 、Gd 3+ 、Ba 2+ 、Bi 3+ 、Ge 4+ 、Ta 5+ 、Yb 3+ 、Li + and Te 4+ One or a combination of two or more.
8. The oxide optical glass according to any one of claims 1 to 7, characterized in that: The density of the oxide optical glass is 4.90 g / cm 3 the following; The wavelength λ when the external transmittance of the oxide optical glass is 70% 70 Below 380nm, the wavelength at which the external transmittance is 5% is below 330nm; The thermal expansion coefficient of the oxide optical glass is α -50 / 80℃ 70×10 -7 / K or less.
9. The oxide optical glass according to any one of claims 1 to 8, characterized in that: The Knoop hardness HK of the oxide optical glass is 650×10 7 Pa or above; The elastic modulus E of the oxide optical glass is greater than 115 GPa.
10. A method for preparing the oxide optical glass according to any one of claims 1 to 9, characterized in that: include: The raw materials of each component are weighed in proportion, mixed evenly, and then melted, and then poured or leaked into a forming mold, or directly pressed into shape.
Citation Information
Patent Citations
Optical glass, glass prefabricated member, optical element and optical instrument with optical element
CN110835229A
Optical glass and preparation method thereof, and optical component
CN111018343A
Optical glass and optical element
CN115321812A
Optical glass and optical element
CN115385569A
Optical glass and optical element
CN116891339A